2016
DOI: 10.4238/gmr.15017540
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and genetic parameter estimates for yield and its components in Jatropha curcas L.

Abstract: ABSTRACT. Jatropha curcas L. is one of the most promising oilseeds for biodiesel and biokerosene production, but few basic studies or breeding programs have been conducted for the species. We estimated genetic parameters and diversity based on 10 yield traits in 77 half-sib progenies of J. curcas after 52 months in the field, and evaluated correlations between them and the oil content of the seeds. The mean grain yield per plant was 377.9 g (ranging from 169.8 to 772.1 g) and the mean oil content was 36.2% (ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 17 publications
2
14
0
Order By: Relevance
“…The lowest seed had 1.71 cm, and the largest, 1.91 cm (Table 1). Reis et al (2015) and Freitas et al (2016) found lengths of seeds very close to those found in the present study, with values varying between 1.68 and 1.94 cm, and an average of 1.80 cm. Already Kaushik et al (2007) found seeds with shorter length, with a minimum of 1.60 and a maximum of 1.76 cm.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The lowest seed had 1.71 cm, and the largest, 1.91 cm (Table 1). Reis et al (2015) and Freitas et al (2016) found lengths of seeds very close to those found in the present study, with values varying between 1.68 and 1.94 cm, and an average of 1.80 cm. Already Kaushik et al (2007) found seeds with shorter length, with a minimum of 1.60 and a maximum of 1.76 cm.…”
Section: Resultssupporting
confidence: 90%
“…Kaushik et al (2007) found a low correlation of 0.23, also confirmed by Reis et al (2015), between the same variables. However, Freitas et al (2016) found that oil content was positively and significantly correlated (0.41) with 100-seed weight. The endosperm area (EA) and the endosperm percentage in the total seed area (EP) were shown to be more efficient to estimating the OC than the MSW.…”
Section: Ms Pinto Et Almentioning
confidence: 91%
“…Bhering et al (2013) found grain yield of 175.95 g, ranging from 57.11 g to 537.10 g, in plants at 20 months of growth. Freitas et al (2016) related an average yield of 377.9 g, ranging from 169.8 g to 772.1 g, at 52 months of cultivation.…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, important instruments for plant breeders have been estimates of genetic parameters and prediction of genetic gain from selection of families and individuals. For this purpose, the REM/BLUP genetic evaluation method, beyond traditional method, has been used in various studies involving families, populations, and clones of J. curcas (Abreu et al 2009, Juhász et al 2010, Freitas et al 2011, Borges et al 2014, Spinelli et al 2014, 2015, Freitas et al 2016.…”
Section: Introductionmentioning
confidence: 99%
“…The worldwide demand for clean, renewable, and sustainable fuels to replace or supplement fossil fuels has made biofuels a great alternative (Freitas et al, 2016). Currently, there are different types of biofuels, especially biodiesel, which can be obtained from any vegetable oil and whose production has strong social, economic, and environmental advantages (Freitas et al, 2011;Santos et al, 2016).…”
Section: Introductionmentioning
confidence: 99%